2020
DOI: 10.1007/s42399-020-00586-5
|View full text |Cite|
|
Sign up to set email alerts
|

Renal Angiomyolipomas with Inferior Vena cava invasion

Abstract: Angiomyolipomas are benign tumors that can occur in the kidneys. Though venous invasion is a common complication of renal cell carcinoma, it rarely occurs with angiomyolipoma given its benign nature. We aim by this article to conduct an extensive literature review documenting rare cases of angiomyolipomas with venous extension, particularly with inferior vena cava invasion. The literature review was conducted following PRISMA checklist, using PubMed searching for English and non-English articles up to January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The first AML associated with IVC invasion was reported in 1982 by Kutcher et al Most cases occur in patients over 40 years old, with the youngest being reported as 16 years old [ 2 ]. To the best of our knowledge, 77 cases of AML include involvement with the IVC, and approximately 75% of all cases of aggressive AML are sporadic and isolated [ 4 , 5 ]. Early detection of AML mainly relies on radiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first AML associated with IVC invasion was reported in 1982 by Kutcher et al Most cases occur in patients over 40 years old, with the youngest being reported as 16 years old [ 2 ]. To the best of our knowledge, 77 cases of AML include involvement with the IVC, and approximately 75% of all cases of aggressive AML are sporadic and isolated [ 4 , 5 ]. Early detection of AML mainly relies on radiological studies.…”
Section: Discussionmentioning
confidence: 99%